Analysis of the demand for reference standards used in quality evaluation of biologicals - V. I. Klimov; E. I. Sakanyan; R. A. Volkova; O. V. Fadeykina; A. A. Movsesyants; E. V. Lebedinskaya; A. P. Shestakova (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Quality evaluation of biologicals entails some specific considerations and problems associated with inherent variability of biological systems. This has implications not only for biological and immunological test methods, but for physical and physico-chemical methods as well. Usage of reference standards (RSs) has an important role to play in the improvement of evaluation of biologicals’ quality. Absence of some industry RSs, which have the status of national RSs, makes it impossible to standardize corresponding products and to assess comparability of test results obtained by different manufacturers for similar (similarly named) products. The first step in the creation of the national system of RSs for medicines is the analysis of the demand for RSs used in quality evaluation of medicines, including biologicals. The analysis of the range of RSs demonstrated that existing industry RSs are not sufficient for performing quality evaluation of available biologicals. At present new industry RSs are being developed.